2016
DOI: 10.4103/0028-3886.177617
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hypoglycemia and its clinical relevance as a prognostic indicator in severe traumatic brain injury: A cerebral microdialysis study from India

Abstract: After decompressive craniectomy in severe TBI, there was a poor correlation between the plasma and CMD glucose concentration. A higher degree of variation was seen in the correlations for individual patients. Neither the mean blood glucose values nor the mean cerebral glucose values predicted the outcome at 3 months. The good outcome group had fewer episodes of both hyperglycemia and hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In the studies by Gupta et al, levels of glutamate were significantly higher in the bad outcome group than the good outcome group: 40.31 µmol/L (SD 67.24) versus 21.68 µmol/L (SD 38.31), p < 0.01. [24][25][26] Recovering trends of glutamate values were seen in the good outcome group over a period of 5 days, consistent with previous studies. 38 This confirms that glutamate could be a useful prognostic marker in TBI.…”
Section: Glutamatesupporting
confidence: 89%
See 4 more Smart Citations
“…In the studies by Gupta et al, levels of glutamate were significantly higher in the bad outcome group than the good outcome group: 40.31 µmol/L (SD 67.24) versus 21.68 µmol/L (SD 38.31), p < 0.01. [24][25][26] Recovering trends of glutamate values were seen in the good outcome group over a period of 5 days, consistent with previous studies. 38 This confirms that glutamate could be a useful prognostic marker in TBI.…”
Section: Glutamatesupporting
confidence: 89%
“…Gupta et al noted that the unfavorable outcome group showed significantly higher episodes of both mitochondrial dysfunction and ischemia than the favorable GOS group: 65.9% versus 55.9% (p < 0.0001); 13.9% versus 7.24% (p < 0.001), respectively. 25,26 These changes were more pronounced with pericontusional catheter placement. The authors compared the results for the time spent in each category, post-resuscitation GCS and age to the GOS score at last follow-up.…”
Section: Mitochondrial Dysfunction and Ischemiamentioning
confidence: 97%
See 3 more Smart Citations